SOSIALISASI PENCATATAN PERKAWINAN DALAM PERATURAN PERUNDANG-UNDANGAN PERKAWINAN DI INDONESIA - Winda Hayati Galuh Pratiwi; Yoyo Hambali; Agus Supriyanto (LPPM Universitas Islam 45, 2022)
Marriage registration is one of the principles of national marriage law that relies on Law No. 1 of 1974 on Marriage. In marriage laws and regulations in Indonesia, the existence of the principle of marriage registration is related to determining the validity of a marriage, meaning that in addition to following the provisions of each religious law or religious beliefs, as well as a condition of the validity of a marriage. Therefore, recording and making marriage certificates is an obligation in marriage laws and regulations in Indonesia. This research aims to add and change people's mindsets about the importance of marriage registration using socialization methods, and community education. As a result of this activity, the community is able to understand the impact and effects of marriages that are not recorded will be declared illegal and will have a negative effect on the legal power for wives and children, the status of children who have been born will be considered as illegitimate children